Empowering EFL Learners’ Pronunciation Skills through the Employment of ELSA Application - kristian (Juliet, 2025)
Abstract The constant activation of effective mobile-assisted language learning applications is deemed a necessary step to respond to the dynamic changes in modern communicative learning enterprises. Previous researchers believed that with the accompaniment of sophisticated digital learning media, language learners can potentially transform into more proficient communicators as they have mastered a wide variety of useful language expressions and words to be efficiently integrated into their communication enterprises. This small-scale library study attempted to investigate the usefulness of the ELSA application in empowering EFL learners’ pronunciation skills. As pronunciation is an inseparable element related to the insistent development of communicative skills, the researcher initiated this investigation to encourage second language educators to be more open-minded and technologically literate in utilizing a vast range of relevant technological learning platforms to improve their learners’ speaking proficiency. To achieve the aforesaid study objective, the researcher employed a thematic analysis approach while analyzing the findings from 30 previous ELSA application journal articles. A thematic analysis approach helped the researcher to yield more accurate, robust, and relevant findings as identical findings were grouped into some main themes. The thematically-categorized findings disclosed that the ELSA application enhanced EFL learners’ pronunciation accuracy and pronunciation learning autonomy. Keywords: MALL, EFL learners, pronunciation, library study, thematic analysis